Megastructures : Super ring
As the world's insatiable need for oil and gas grows, companies are digging deeper, in more hostile environments than ever before. It's a never-ending race that's pushing technology to breaking point. In the Gulf of Mexico, one of the largest ultra-deep water rigs in the world is towed into place just in time for hurricane season. In the North Atlantic, a gigantic offshore platform stands in the path of the annual iceberg migration. We rip apart the largest oil rigs on the planet to reveal the secrets of these amazing technological achievements and discover if they can survive Mother Nature's most violent forces.